Activation of sulphonylurea-sensitive channels and the NO-cGMP pathway decreases the heart rate response to sympathetic nerve stimulation. - Mohan, R; Paterson, D (2000)
OBJECTIVES: Activation of ATP sensitive K+ channels (K(ATP)) and the NO-cGMP pathway have both been implicated in reducing norepinephrine (NE) release from cardiac sympathetic nerves during stimulation. Our aim was to test whether these pathways could interact and modulate cardiac excitability during sympathetic nerve stimulation (SNS). METHODS: The effect of inhibitors and activators of K(ATP) channels and the NO-cGMP pathway on the heart rate (HR) response to cardiac SNS in the isolated guinea pig (Cavia porcellus) double atrial/right stellate ganglion preparation was studied (n=48). RESULTS: The K(ATP) channel activator, diazoxide (100 microM, n=6) or hypoxia (0% O2/5% CO2, n=6) significantly attenuated the HR response to 3 Hz SNS by -10+/-4% and -27+/-6% respectively; an effect that was reversed by the K(ATP) channel inhibitor, glibenclamide (30 microM). Glibenclamide (n=6) on its own enhanced the HR response to SNS by 20+/-8%. Bath applied NE (0.1-0.7 microM, n=6) did not affect the HR response to diazoxide, although an increased response to glibenclamide was observed at 0.3 and 0.5 microM NE. In the presence of 8-Br-cGMP (0.5 mM, n=7), diazoxide further decreased the HR response SNS (19+/-3%). The NO synthase inhibitor, N-omega-nitro-L-arginine (100 microM) significantly increased the HR response (13+/-3%) to SNS in the presence of diazoxide (100 microM, n=6). This effect was reversed with excess (1 mM) L-arginine. Conversely, the NO donor, sodium nitroprusside (SNP, 20-100 microM) significantly attenuated the HR response to SNS. The addition of glibenclamide (30 microM, n=10) could still enhance the HR response (42+/-15%) to SNS. Similar results were seen with the cyclic GMP analogue, 8-Br-cGMP (0.5 mM, n=12). CONCLUSIONS: Our results indicate that NO and sulphonlyurea-sensitive channels act in a complementary fashion, but appear to be independent of each other in the regulation of HR during cardiac SNS activation.